Formation of valeological competence in conditions of classroom and distance learning - Shevchenko, A. S.; Kucherenko, Serhii; Komyshan, Anatolii; Shevchenko, V. V.; Kucherenko, Nataliia (Харківськии̮ національнии̮ університет ім. В. Н. Каразіна, 2022)
Formulation of the problem. The article considers the problem of valeological (health saving) competence formation in non-medical students. Health saving competencies are based on a healthy lifestyle, safe behavior practices and the ability to provide emergency pre-hospital care to victims in critical situations. The formation of valeological competence in non-medical takes place during the study of valeological disciplines (including “Fundamentals of Medical Knowledge”, “Health Pedagogy” and others) in higher education institutions (HEI). Since the spring of 2019, the teaching of these disciplines is forced to take place in distance form.
Формування валеологічно ї компететності в умовах аудиторного та дистанційного навчання
Keywords: health saving; "Health Pedagogy"; "Fundamentals of Medical Knowledge"; qualimetric model; factor-criterion analysis; здоров'язбереження; "Педагогіка здоров'я"; "Основи медичних знань"; кваліметрична модель; факторно-критеріальний аналіз